Prevalence of and Risk Factors for Self-Reported Chronic Bronchitis in a Canadian Population: The Canadian Community Health Survey, 2007 To 2008 - Chandima Karunanayake; Briana Hagen; James Dosman; Punam Pahwa (Canadian Respiratory Journal)
BACKGROUND: Chronic bronchitis (CB) represents one of the respiratory disease phenotypes that affect the Canadian health care system significantly. Presently, almost 6.5% of total health care costs are related to respiratory diseases.